2020
DOI: 10.21203/rs.3.rs-88677/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation Between Quantitative Perfusion Histogram Parameters of DCE-MRI and PTEN, P-Akt and m-TOR in Different Pathological Types of Lung Cancer

Abstract: Background: To explore if the quantitative perfusion histogram parameters of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) correlates with the PTEN, P-Akt and m-TOR protein in lung cancer.Methods: Thirty‐three patients with 33 lesions who had been diagnosed with lung cancer were enrolled in this study. They were divided into three groups: squamous cell carcinoma (SCC, 15 cases), adenocarcinoma (AC, 12 cases) and small cell lung cancer (SCLC, 6 cases). Preoperative imaging (conventional imaging… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Our results showed that there was a statistical difference in the expression level of Ki-67 index in patients with 3 different pathological types of lung cancer (H=103.762, P=0.000). The results are similar to those reported by previous researchers ( 14 ). It also indicates that the participants in our study are suitable for further study of the correlation analysis between Ki-67 index and image features.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that there was a statistical difference in the expression level of Ki-67 index in patients with 3 different pathological types of lung cancer (H=103.762, P=0.000). The results are similar to those reported by previous researchers ( 14 ). It also indicates that the participants in our study are suitable for further study of the correlation analysis between Ki-67 index and image features.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies of MRI mainly focus on malignant tumor such as breast cancer and lung cancer. Scholars have found that there was a negative relationship between ADC and Ki-67 index (11)(12). Therefore, the ADC has the potential to re ect the growth of the tumor cell to a certain extent while it is limited as an alternative marker to re ect the proliferation potential (13).…”
Section: Introductionmentioning
confidence: 99%